Investigating the Influence of Tacit Knowledge Transformation Approach on Students’ Learning Ability - Zheyu, Liu; Weijin, Cui; Jihui, Zhou; Yuan, Wang; Ghani, Usman; Zhai, Xuesong (Frontiers in Psychology, 2021)
Tacit knowledge is an essential foundation for developing students’ learning skills, especially in understanding and solving problems. Transforming tacit knowledge is one of challenge in student ability development practices which affect students’ sense of well-being in learning. This problem became even more pronounced during the outbreak of Corona Virus Disease 2019 (COVID-19), because the massive spread of social media resulted in the neglect of face-to-face interaction. This study designed and applied a tacit knowledge transformation model to promote students’ ability of understanding and solving problems, while creates a positive classroom climate to enhance students’ well-being. To assess the effectiveness of the model, this study conducted a comparative experiment with 60 elementary school students who were randomly divided into two groups. The group using the tacit knowledge transformation model showed the enhanced ability to understand and solve problems. The results not only demonstrated the effectiveness of the model in improving students’ learning ability, but also provide an implementable model that helps teachers to organize instructional activities, thereby advocate the appropriate use of social media.